MENTAL HEALTH AND WELLBEING IN THE POLICE AND EMERGENCY SERVICES SECTOR - David Lawrence (The Journal of Intelligence, Conflict and Warfare, 2023)
On November 23, 2022, David Lawrence, Professor of Mental Health in the School of Population Health at Curtin University & Adjunct Professor in the School of Population and Global Health at the University of Western Australia, presented on Mental Health and Wellbeing in the Police and Emergency Services Sector. Following the presentation, a question-and-answer period ensued with questions from the audience and CASIS Vancouver executives. The key points discussed were experiences by retired service personnel, and generational attitudes among police and Emergency Medical Services (EMS) towards mental health conditions.